Discourses of Freedom of Speech - Rudanko, J. author. aut Link
VII, 201 p.
Keywords: Freedom of speech is a tradition distinctive to American political culture, and this book focuses on major debates and discourses that shaped this tradition. It sheds fresh light on key Congressional debates in the early American Republic, developing and applying an approach to fallacy theory suitable to the study of political discourse.